Harmonic distortion assessment in power distribution networks considering DC component injection from PV inverters - Fortes, Rarison R. A.; Buzo, Ricardo F. [UNESP]; Oliveira, Luis C. O. de [UNESP] (Elsevier B.V., 2020)
The large-scale connection of distributed generation (DG) units imposes on utilities a series of technical, economic, and regulatory challenges required to ensure the reliability and the power quality in the distribution networks. One of the technical problems refers to the harmonic current levels caused by inverters employed in photovoltaic distributed generation (PV), increasing the possibility of resonance in systems with capacitors. In addition, inverters without isolation transformer can also inject a certain amount of DC current which, being present in power transformer secondary windings, favor the generation and propagation of additional harmonics in the primary side. Thus, this paper shows that DC currents injected by PV inverters create one more condition that may cause system-capacitor resonance. For this, laboratory analyses are presented showing the conditions under which different models of PV inverters inject a higher DC current level. As a result, it is verified that higher DC current level is injected in conditions different from those in which there is higher harmonic current injection, concluding that the inverter may affect the power quality for whatever the power injected by the PV system.
Keywords: Direct current; Distributed generation; Power transformer; Harmonic current; Resonance